1997
DOI: 10.1128/jb.179.9.2879-2883.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipoteichoic acid on thermotropic membrane properties

Abstract: Lipoteichoic acid, diglucosyldiacylglycerol, and phosphatidylglycerol isolated from Staphylococcus aureus were embedded in dipalmitoylglycerophosphoglycerol vesicles, and their thermotropic influence on this matrix was studied by differential scanning calorimetry. The natural fatty acids of phosphatidylglycerol effected peak broadening and a decrease in molar heat capacity. These effects were more pronounced with the glycolipid, which also increased the main transition temperature. With the lipoteichoic acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…1). Assuming that LTA makes up about 2% of the dry cell weight [19], 20 g LTA would equate to several billion staphylocci, numbers well above the numbers found in mastitic udders. Nevertheless, LTA is likely to be of biological significance because (i) recent data indicate that the physical presentation of LTA (such as immobilization on a solid surface) increases LTA activity by several orders of magnitude [11]; and (ii) LTA can act synergistically with other PAMP, which could still lower the amount required to induce inflammation by an order of magnitude.…”
Section: Discussionmentioning
confidence: 96%
“…1). Assuming that LTA makes up about 2% of the dry cell weight [19], 20 g LTA would equate to several billion staphylocci, numbers well above the numbers found in mastitic udders. Nevertheless, LTA is likely to be of biological significance because (i) recent data indicate that the physical presentation of LTA (such as immobilization on a solid surface) increases LTA activity by several orders of magnitude [11]; and (ii) LTA can act synergistically with other PAMP, which could still lower the amount required to induce inflammation by an order of magnitude.…”
Section: Discussionmentioning
confidence: 96%
“…Micelles with a decreased LTA concentration do not trap or sequester autolysins, and therefore the inhibitory action of LTA that had originally been described with high-density micelles may have led to an equivocal conclusion. A molecule of membraneassociated LTA in the cell is surrounded, on average, by eight phospholipid molecules (195). Under these conditions, LTA binds autolysin for presentation to the susceptible peptidoglycan linkages.…”
Section: D-alanyl Esters In Autolysin Controlmentioning
confidence: 99%
“…18) with a type I LTA in the absence of other wall components, e.g., peptidoglycan. In a biophysical analysis of type I LTA, Gutberlet et al (195) observed two types of interaction that occur with LTA in vesicles of dipalmitoyl-sn-glycero-3-phospho-1-glycerol (DPPG) at high ionic strength. The first occurs between the glucosyl hydroxyl groups of the LTA glycolipid anchor and the phosphoglycerol moiety of adjacent DPPG.…”
Section: Supramolecular Organization Of Lta and The Nacl-activated D-mentioning
confidence: 99%
“…Lipoteichoic acid (LTA) is a candidate-hindering component that is removed by this treatment, as it seems to be present in L. lactis at those positions where AcmA is not able to bind (49). LTA is a secondary cell wall polymer suggested to be involved in the control of autolysin activity (5,15), in determining the electrochemical properties of the cell wall (42), in establishing a magnesium ion concentration (2, 21, 26, 31), and in determining the physicochemical properties of the cytoplasmic membrane (18). LTA can be modified by various compounds, such as glycosyl residues (15) and D-Ala esters (1).…”
mentioning
confidence: 99%